Mass gathering and globalization of respiratory pathogens during the 2013 Hajj - Memish, Z.A. (Clin Microbiol Infect, 2015)
Every year, more than 10 million pilgrims arrive in the Kingdom of Saudi Arabia for the Hajj or Umrah. Crowding conditions lead to high rates of respiratory infections among the pilgrims, representing a significant cause of morbidity and a major cause of hospitalization. Pre- and post-Hajj nasal specimens were prospectively obtained from a paired cohort (692 pilgrims) and from nonpaired cohorts (514 arriving and 470 departing pilgrims) from 13 countries. The countries of residence included Africa (44.2%), Asia (40.2%), the United States (8.4%) and Europe (7.2%). Nasal specimens were tested for 34 respiratory pathogens using RT-PCR. A total of 80 512 PCRs were performed. The prevalence of viruses and bacteria increased, from 7.4% and 15.4% before the Hajj to 45.4% and 31.0% after the Hajj, respectively, due to the acquisition of rhinovirus, coronaviruses (229E, HKU1, OC43), influenza A H1N1, Streptococcus pneumoniae, Haemophilus influenzae and Staphylococcus aureus. We did not identify Middle East respiratory coronavirus carriage. At arrival, the prevalence of several viruses was clearly dependent on the pilgrim's country of origin. After Hajj participation, these viruses were isolated among pilgrims from all countries, with few exceptions. No significant differences were observed between paired and nonpaired cohort results. Our results strongly suggest that, given the particularly crowded conditions during the rituals, an international mass gathering such as the Hajj may contribute to the globalization of respiratory pathogens after the cross-contamination of pilgrims harbouring pathogens that easily spread among participants. Influenza and pneumococcal vaccination, face mask use and hand hygiene should be considered in the context of the Hajj.